2004
DOI: 10.1108/13527600410797729
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐cultural comparison of organizational culture: evidence from universities in the Arab world and Japan

Abstract: A cross-cultural comparison of organizational culture: evidence from universities in the Arab world and Japan Evangellos Dedoussis Article information:To cite this document: Evangellos Dedoussis, (2004),"A cross-cultural comparison of organizational culture: evidence from universities in the Arab world and Japan", CrossIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…Studies have shown that despite the heterogeneity of organisational cultures within one country, they themselves are affected by the national culture (Soeters and Schreuder, 1988;Hofstede et al, 1990in Parboteeah et al 2005. This was supported by Dedoussis (2004) who claimed that:…”
Section: Introductionmentioning
confidence: 76%
“…Studies have shown that despite the heterogeneity of organisational cultures within one country, they themselves are affected by the national culture (Soeters and Schreuder, 1988;Hofstede et al, 1990in Parboteeah et al 2005. This was supported by Dedoussis (2004) who claimed that:…”
Section: Introductionmentioning
confidence: 76%
“…However, adopting or simply understanding, a US-centered perspective of the world may present a challenge to foreign faculty with limited exposure to American culture. The challenge is even greater for third-country faculty as American universities abroad are not pure transplants of the US model but their operations are influenced by the host country's socio-cultural environment thus developing a complex and peculiar 'localized American' identity (Dedoussis, 2004) difficult for third-country faculty to understand and reconcile with their own perceptions of what an 'American' university ought to look like. As one German colleague, leaving AUB to join an American university in Germany, commented:…”
Section: Diversity In Academia: Options and Responsesmentioning
confidence: 97%
“…The result indicated that there is tendency toward participative and consultative styles in decision making. However, although consultative and participative styles are the most common decision-making styles in Arab culture, decisions are taken without subordinates and are not delegated down the hierarchy (see Dedoussis 2004). It has been argued (Tayeb 1997) that participation in decision making might be considered by subordinates as a management weakness in Arab culture and further, managers and subordinates in Arab societies tend to dislike teamwork.…”
Section: Arab Culture and The Workplacementioning
confidence: 99%